Analysis of the influence of compensation organizational culture, and work discipline on the performance of lecturer Surabaya Shipping Polytechnic (Research, Society and Development, 2020)
The existance of human resources in an educational institution plays a very important role. Educators have great potential to carry out the activities of educational/ school institutions. The potential of every human resource in an educational/ school institution must be utilized as well as possible so as to be able to provide output/ graduates with optimal abilites.In this study it is known (X1), cmpensation (X1) has a significant effect, which is indicated by a significance value of 0.025 count less than 0.05 (5%), the variable Organizational Culture (X2) does not have a significant effect with a significant value of 0.208 greater from 0.05 (5%), work discipline (X3) with a significant value of 0.014 smaller than 0.05 (%) which means that work discipline effects the performance of Surabaya Shipping Polytechnic Educators.